(untitled) (Journal of Social Sciences Review, 2023)
According to grounded social exchange theory, this study examines ethical leadership’s direct and indirect impact on worker’s creative performance. More specifically, this study will also investigate the intervening mediate roles of work engagement and employee’s attitudes towards performing well between Ethical leadership and Creative work performance. The study data was obtained through self-reporting survey questionnaires distributed to employees of construction organizations in Lahore, Pakistan. The findings supported that Ethical leadership directly relates to creative work performance. Furthermore, work engagement and attitude toward performing well positively relate to ethical leadership and creative work performance. The findings broaden our understanding of how factors such as a positive attitude, psychological states, and engagement at work may produce the worker’s performance and increase their potential for creative intellectual in implementing novel ideas at the workplace.